Itinerários de sujeitos no contexto do cracke as variações do cuidado - Heise, Maira [UNIFESP] (2015)
The use of drugs is characterized as present practice since the beginning of mankind and currently its abuse achieved worrying dimensions, setting a picture as a public health problem. Care becomes one of the major axis driversof public policies aimed at people who use crackand its driving gains a variety of meanings that comes to the scene. The theme of this research is inserted in this context which investigated and analyzed the intinerary of the individuals who are crackusers and care demonstrations from their experience in the streets. This is a qualitative research using the ethnographic method using the document research and the participant observation as tools for recognizing the reality and valuation of the marked individuals through meetings held within five months of observation. Also, evaluations were prepared targeting deepening the knowledge of individuals. The field diaries were the main drivers of the entire analytical process using the analysis and interpretation of the information used to Depth Hermeneutics. The information was organized from the three levelsof analysis: social and historical analysis, formal analysis andinterpretation / reinterpretation. From this methodological reference emerged three axes which contribute to a better understanding of the itineraries: path of life and care, experience and office in the streets and the subjective production of care. It was noticed that the itineraries of those who use crackare a complex phenomenon to be subsumed into generality. The itineraries are simultaneous and natural resulting of life trajectories, variations in care expressions and contexts of different relationships which involve people as well as communities and institutions. Daily follow-up also allowed us an enlarged view of health care aiming promoting actions of life and the valuation of good meetings in micro political spaces.